Influence of sowing dates on stemphylium blight disease severity and yield performance of lentil at Rampur, Chitwan, Nepal - Subedi, S.; Shrestha, S. M.; Khatri-Chhetri, G. B.; Thapa, R. B.; Ghimire, S. K.; Gharti, D. B.; Neupane, S. (Journal of the Institute of Agriculture and Animal Science, 2018)
A study on lentil (Lens culinaris Medik) was carried out at Rampur, Chitwan with different sowing dates under field conditions to assess the severity of Stemphylium blight disease severity and yield performance during two consecutive years 2012-2014. During 2012/013, lower (3.00) and higher disease severity (6.50) were recorded on lentil plants sown on November 6 and December 16, respectively. Early sown lentil resulted in higher yield (2025 kg/ha) followed by late shown one (1213 kg/ha). Similarly, trends of disease development were similar in succeeding year (2013/14). Lentil seed shown on November 1 had lower disease severity (3.50) and produced higher yield (962.50 kg/ha) compared to that were shown on later dates. Disease severity increased with the advancement of sowing date from November 1 to December 21 with decreased yields. Hence, over years, early shown lentil (November 1, 6 and 11) escaped the higher severity of Stemphylium blight with the increase in yield. Journal of the Institute of Agriculture and Animal Science. Vol. 33-34, 2015, Page: 129-136